2017
DOI: 10.1016/j.jhydrol.2016.11.053
|View full text |Cite
|
Sign up to set email alerts
|

Developing and testing a global-scale regression model to quantify mean annual streamflow

Abstract: Quantifying mean annual flow of rivers (MAF) at ungauged sites is essential for assessments of global water supply, ecosystem integrity and water footprints. MAF can be quantified with spatially explicit process-based models, which might be overly time-consuming and data-intensive for this purpose, or with empirical regression models that predict MAF based on climate and catchment characteristics. Yet, regression models have mostly been developed at a regional scale and the extent to which they can be extrapol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…Data-driven approaches have been mostly employed at a local scale 34 . Recent studies demonstrated, however, the feasibility of applying a data-driven approach at a global scale, resulting in streamflow estimates that may have greater accuracy than the output of GHMs/LSMs 31 , 32 . Despite these encouraging results, consistent high-resolution global streamflow maps are not yet available.…”
Section: Background and Summarymentioning
confidence: 99%
“…Data-driven approaches have been mostly employed at a local scale 34 . Recent studies demonstrated, however, the feasibility of applying a data-driven approach at a global scale, resulting in streamflow estimates that may have greater accuracy than the output of GHMs/LSMs 31 , 32 . Despite these encouraging results, consistent high-resolution global streamflow maps are not yet available.…”
Section: Background and Summarymentioning
confidence: 99%
“…We quantified species-specific thresholds for minimum and maximum weekly flow, maximum number of zero flow weeks and maximum and minimum weekly water temperature based on the present-day distribution of these characteristics within the geographic range of each species, similarly to previous studies 45 , 49 , 50 . To this end, we overlaid the species’ range maps with the weekly flow and water temperature metrics from the output of the hydrological model, calculated for each year and averaged over a 30-years historical period to conform to the standard for climate analyses 51 , 52 (1976–2005, for each GCM employed in the study). We calculated for each 5 arcminutes grid cell the long-term average minimum and maximum weekly flow ( Q min , Q max , Eqs.…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, there have only recently been a few studies [48,49] focusing on mapping high-resolution global river discharge. Barbarossa et al [48] have developed a global-scale regression model to quantify the mean annual discharge based on the observations of discharge and river basin characteristics from 1885 river basins worldwide, and this model can be applied globally to estimate the mean annual discharge at any point of the river network.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there have only recently been a few studies [48,49] focusing on mapping high-resolution global river discharge. Barbarossa et al [48] have developed a global-scale regression model to quantify the mean annual discharge based on the observations of discharge and river basin characteristics from 1885 river basins worldwide, and this model can be applied globally to estimate the mean annual discharge at any point of the river network. Moreover, Barbarossa et al [49] have created FLO1K, a consistent discharge dataset at a resolution of 30 arc seconds (~1 km) and global coverage, by means of artificial neural networks regression using the observations of discharge from 6600 monitoring stations worldwide.…”
Section: Discussionmentioning
confidence: 99%